2017
DOI: 10.1111/cns.12716
|View full text |Cite
|
Sign up to set email alerts
|

The pathological roles of NDRG2 in Alzheimer's disease, a study using animal models and APPwt‐overexpressed cells

Abstract: Our study confirmed the upregulation of NDRG2 in AD animal models and demonstrated its important roles in AD pathology. NDRG2 might be a potential target for studying and treatment of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…might play a role in generating Aβ [44]. Collectively, the 15 genes are not significantly enriched to be involved with any biological pathway; however, individually, these genes may play an essential role in the pathological aspect of AD and may provide new therapeutic targets for disease intervention.…”
Section: Discussionmentioning
confidence: 99%
“…might play a role in generating Aβ [44]. Collectively, the 15 genes are not significantly enriched to be involved with any biological pathway; however, individually, these genes may play an essential role in the pathological aspect of AD and may provide new therapeutic targets for disease intervention.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the deficiency of innate immune ability to clear Aβ deposits (rather than overproduction of them) has been widely accepted as one of the most important causes of AD pathogenesis, and current research was gradually moved from blocking the production of Aβ deposits to rebalancing the immune system of AD patients . For example, interleukin (IL)‐10, one of the best known inflammatory cytokines, was a major regulator of macrophages .…”
Section: Introductionmentioning
confidence: 99%
“…NDRG2 may function in synapse formation, neural differentiation, and axon survival in response to glucocorticoids (Deng et al 2003;Nichols et al 2005). Prior studies confirmed the increase of NDRG2 levels in AD dystrophic neurons and senile plaques (Mitchelmore et al 2004) as well as APP/PS1 transgenic mice brains (Rong et al 2017). The SNO sites described in this study (amino acid position 255 and 274) have been previously identified in an experiment utilizing induced nitrosylation, but the functional consequences of these modifications are unknown (Kohr et al 2012).…”
Section: Discussionmentioning
confidence: 92%